2015
DOI: 10.1089/ther.2014.0020
|View full text |Cite
|
Sign up to set email alerts
|

Localized Hypothermia Aggravates Bleeding in the Collagenase Model of Intracerebral Hemorrhage

Abstract: Animal studies testing whether therapeutic hypothermia is neuroprotective after intracerebral hemorrhage (ICH) have been inconclusive. In rodents, ICH is often produced in the striatum by infusing collagenase, which causes prolonged hemorrhaging from multiple vessels. Our previous data shows that this bleeding (hematoma) is worsened by systemic hypothermia given soon after collagenase infusion. In this study we hypothesized that localized brain hypothermia would also aggravate bleeding in this model (0.2 U of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…We have repeatedly used this technique to monitor minute-by-minute ICP changes in freely moving rats over several days [7, 1316]. In addition, we tested whether acetazolamide affects hematoma formation because it can acutely increase cerebral blood flow [17], and early interventions can aggravate bleeding after collagenase-induced ICH [18]. Finally, we assessed effects of acetazolamide on behavioral and histological outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We have repeatedly used this technique to monitor minute-by-minute ICP changes in freely moving rats over several days [7, 1316]. In addition, we tested whether acetazolamide affects hematoma formation because it can acutely increase cerebral blood flow [17], and early interventions can aggravate bleeding after collagenase-induced ICH [18]. Finally, we assessed effects of acetazolamide on behavioral and histological outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Although not part of our initial hypothesis, the most interesting and concerning result of this study is the influence of TH on bleeding post-treatment, since the hematoma volume is a critical predictor of outcome and survival. 49,50 Previous studies show that TH applied too early can aggravate bleeding, 22,25 which we successfully avoided by delaying treatment, as we have previously done. 24 As there were no group differences in hematoma volume at 1 and 3 days post-ICH, the increase seen on day 7 is likely due to re-bleeding either during rewarming or over the following days.…”
Section: Discussionmentioning
confidence: 87%
“…for hemoglobin levels after ICH the average standard deviation (S.D.) was $15 after ICH, 25 and for non-heme iron the SD was 1.2 on day 3 after ICH 38 ). From that we roughly obtain estimates for effect sizes and variability with the goal of having 80% power to detect those effects.…”
Section: Animals and Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…TH can affect hemostasis by inhibiting clotting factors and altering platelet function (Alam et al , 2012 ). We showed that prolonged hypothermia (HYPO) aggravates bleeding in the collagenase ICH model (John et al , 2015 ). Therefore, depth, duration, and onset of TH must be considered when TH is used in populations with a high risk of hemorrhage.…”
Section: Introductionmentioning
confidence: 99%